Power of ANCOVA vs change-score model in a quasi-experimental design in education - Balagtas, Marilyn Ubiña (2005)
This study investigated the relative statistical power of Analysis of Covariance (ANCOVA) and Change-Score Model (CSM) in determining the effects of the treatment variable on the dependent variable in experimental studies using the nonequivalent pretest-posttest control group design. It employed a descriptive-comparative research method in which 30 quasi-experimental studies conducted from 1992 to 2003 were described in terms of their substantive and research methodological characteristics. It was revealed that the mean ES values for both ANCOVA and CSM are higher when alpha and beta are set at a lower level but the ES values for CSM are greater than those for ANCOVA regardless of the alpha and beta level.
"October, 2005."
Thesis (Ph.D. Research and Evaluation)--University of the Philippines, Diliman.
Keywords: Education -- Research -- Philippines; Analysis of variance; Analysis of covariance; Experimental design